2019
DOI: 10.3390/nu11112771
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition-Inflammation Score VS Phase Angle in the Era of GLIM Criteria: A Cross-Sectional Study among Hemodialysis Patients in UAE

Abstract: (1) Background: Malnutrition is prevalent in hemodialysis (HD) patients and is associated with an increased risk of morbidity and mortality. The aim of this study was to explore the prevalence of malnutrition using the malnutrition-inflammation score (MIS) and phase angle (PhA) and compare their concordance with the new Global Leadership Initiative on Malnutrition (GLIM) criteria for the diagnosis of malnutrition. (2) Methods: Seventy HD patients were assessed. Malnutrition was diagnosed based on the GLIM crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
2
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 31 publications
(42 reference statements)
2
23
2
4
Order By: Relevance
“…This variability resulted only in a fair agreement between 7p-SGA and MIS with GLIM, with poor diagnostic accuracy for GLIM, characterized by AUC ranging from 0.61 to 0.68. This finding is similar to that found by Karavetian et al 15 in which there was a fair agreement between GLIM and MIS (kappa 5 0.202) and a higher prevalence of malnutrition by GLIM (54.3%) than by MIS (48.6%) in adult MHD patients. The difference in structure between the tools likely played an important role in these findings.…”
Section: Discussionsupporting
confidence: 90%
“…This variability resulted only in a fair agreement between 7p-SGA and MIS with GLIM, with poor diagnostic accuracy for GLIM, characterized by AUC ranging from 0.61 to 0.68. This finding is similar to that found by Karavetian et al 15 in which there was a fair agreement between GLIM and MIS (kappa 5 0.202) and a higher prevalence of malnutrition by GLIM (54.3%) than by MIS (48.6%) in adult MHD patients. The difference in structure between the tools likely played an important role in these findings.…”
Section: Discussionsupporting
confidence: 90%
“…Karavetian et al. (2019) according to the ROC cutoff points, Chi‐square test was conducted between PEW and non‐PEW groups. OR and 95% CI were calculated in prediction of PEW.…”
Section: Discussionmentioning
confidence: 99%
“…Considering M-BIA as predictor in the evaluation of health in populations (Norman et al, 2012;Powrózek et al, 2019;, our result also indicated that PA can be used as independent factor associated with malnutrition in CKD patients. Karavetian et al (2019)…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Global Leadership Initiative on Malnutrition (GLIM), a set of guidelines for diagnosing malnutrition, was proposed 18 . Previous studies proved the effectiveness of these guidelines in identifying malnutrition 20‐22 . However, validation of the value of the GLIM guidelines in cancer patients remains scare 23 .…”
Section: Introductionmentioning
confidence: 99%
“…18 Previous studies proved the effectiveness of these guidelines in identifying malnutrition. [20][21][22] However, validation of the value of the GLIM guidelines in cancer patients remains scare. 23 And there has not been a study that has evaluated its role in determining the prognosis of LC patients.…”
Section: Introductionmentioning
confidence: 99%